Acoustic performance of dual-electrode electrostatic sound generators based on CVD graphene on polyimide film. (7th June 2018) - Lee, Kyoung-Ryul; Jang, Sung Hwan; Jung, Inhwa
Abstract: We investigated the acoustic performance of electrostatic sound-generating devices consisting of bi-layer graphene on polyimide film. The total sound pressure level (SPL) of the sound generated from the devices was measured as a function of source frequency by sweeping, and frequency spectra were measured at 1/3 octave band frequencies. The relationship between various operation conditions and total SPL was determined. In addition, the effects of changing voltage level, adding a DC offset, and using two pairs of electrodes were evaluated. It should be noted that two pairs of electrode operations improved sound generation by about 10 dB over all frequency ranges compared with conventional operation. As for the sound-generating capability, total SPL was 70 dBA at 4 kHz when an AC voltage of 100 Vpp was applied with a DC offset of 100 V. Acoustic characteristics differed from other types of graphene-based sound generators, such as graphene thermoacoustic devices and graphene polyvinylidene fluoride devices. The effects of diameter and distance between electrodes were also studied, and we found that diameter greatly influenced the frequency response. We anticipate that the design information provided in this paper, in addition to describing key parameters of electrostatic sound-generating devices, will facilitate the commercial development of electrostatic sound-generating systems.